A patient-specific wear prediction framework for an artificial knee joint with coupled musculoskeletal multibody-dynamics and finite element analysis. (May 2017) - Zhang, Jing; Chen, Zhenxian; Wang, Ling; Li, Dichen; Jin, Zhongmin
Abstract: A novel wear prediction framework was developed by coupling a patient-specific lower extremity musculoskeletal multibody dynamics model with the finite element contact mechanics and wear model of total knee replacement. The tibiofemoral contact forces and kinematics were influenced by articular surface wear, and in turn, the variations from the knee dynamics resulted in increases in the volumetric wear of 404.41 mm 3 after 30 million cycle simulation from 380.86 mm 3 from the traditional wear prediction using fixed load/motions. The developed patient-specific wear prediction framework provided a reliable virtual platform for investigating articular surface wear of total knee replacements. Highlights: A novel patient-specific wear prediction framework was developed. Coupling a patient-specific musculoskeletal model and finite element wear model. Knee loads and motions were influenced by the tibial insert wear. Varied knee contact mechanics further aggravated the tibial insert wear.